Cultivating emotions: a rhetorical and agonistic framework for political passion. - Serra, Mauro (Rivista Italiana di Filosofia del Linguaggio, 1970)
The role of passions in politics is paradoxical. They are traditionally considered a threat, but at the same time, also as a result of research in neuroscience, we recognize more and more that we can’t do without them. Hence a stalemate well represented by the relationship between the two main conceptions of democracy, agonistic democracy and deliberative democracy. The former appeals to the passions but without being able to explain how to urge them without being a victim of them, the latter describes a reason free from passions, but has the problem of engaging citizens and can be susceptible to the charge of motivational impotence. Faced with this situation, rhetoric seems to be a discipline that can provide a theoretical framework to connect fruitfully reason and passions in political sphere. This framework has three distinctive features: the role of doxa (belief) as link between reason and passions, an agonistic conception of truth, a tragic view of world based on a deep awareness of the limits of human reason and the belief that rhetorical action is the means by which identities become temporarily enacted and forged in response to the needs of a specific contingent situation.